Design of new quadruplexer with compact size, high isolation and wide stopband. Issue 1 (January 2015) - Wu, Hung-Wei; Huang, Shih-Hua
Abstract This study presents a quadruplexer (1.8/2.4/3.5/5.8 GHz) with compact size, high isolation, low insertion loss and wide stopband based on the multi-mode resonators. The quadruplexer is composed of four pairs of coupled multi-mode resonators (uniform impedance resonator, UIR and stepped impedance resonators, SIRs) and the source–load coupling lines. Each channel (passband) can be easily determined by tuning the impedance ratio (K) and length ratio (α) of the SIRs so as to implement a 2-order bandpass filter individually. The source–load coupling lines are designed to correspond to the quarter-wavelength of the center frequency at each channel. The proposed quadruplexer shows a simple configuration, an effective design method and a small circuit size.